New Headway. Upper-Intermediate. Teachers Resource Book. - Cooke, Joanna and Hudson, Jane (Oxford Oxford University Press, 2002)
New Headway English Course is a development of the highly successful multi-level Headway series. The course combines the best of traditional methods with more recent approaches to help students use English accurately and fluently, and provides a fully comprehensive language teaching series from beginner to advanced.
Keywords: EFL